2016
DOI: 10.1101/067876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An RNA-binding tropomyosin recruits kinesin-1 dynamically tooskarmRNPs

Abstract: Localization and local translation of oskar mRNA at the posterior pole of the Drosophila oocyte directs abdominal patterning and germline formation in the embryo. The process requires precise recruitment and regulation of motor proteins to form transport-competent mRNPs.Using high-and super-resolution imaging, we determine the steps in motor recruitment to oskar mRNPs. We show that the posterior-targeting kinesin-1 is recruited upon nuclear export of oskar mRNPs, prior to their dynein-dependent transport from … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 66 publications
0
38
0
Order By: Relevance
“…Why is proper deposition of germ granules at the posterior pole of Drosophila oocytes dependent on Tm1-I/C-specified intermediate filaments? Visualization of a GFP-tagged form of Tm1-I/C in living oocytes has shown that the protein becomes precisely restricted to the posterior tip of oocytes well before the completion of polar granule deposition (8). We speculate that assembled Tm1-I/C intermediate filaments localized to the posterior pole of fly oocytes might constitute a Velcro-like landing pad for one or more of the constituent RNA-binding proteins specifying polar granules.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Why is proper deposition of germ granules at the posterior pole of Drosophila oocytes dependent on Tm1-I/C-specified intermediate filaments? Visualization of a GFP-tagged form of Tm1-I/C in living oocytes has shown that the protein becomes precisely restricted to the posterior tip of oocytes well before the completion of polar granule deposition (8). We speculate that assembled Tm1-I/C intermediate filaments localized to the posterior pole of fly oocytes might constitute a Velcro-like landing pad for one or more of the constituent RNA-binding proteins specifying polar granules.…”
Section: Discussionmentioning
confidence: 89%
“…Perplexingly, mutations proximal to the locus encoding the fly tropomyosin gene also impede the deposition of germ granules and subsequent formation of germ cells (6). These mutations interfere with the formation of a nonmuscle isoform of tropomyosin, designated Tm1-I/C, that is somehow required for germ cell specification (7,8).…”
mentioning
confidence: 99%
“…In a second step, gurken RNA is subsequently transported to the dorsal-anterior corner of the oocyte along microtubules nucleated by the oocyte nucleus (MacDougall et al, 2003). Localization of oskar mRNA to the posterior of the oocyte relies instead on the plus-end directed microtubule motor, kinesin (Brendza et al, 2000;Cha et al, 2002;Gáspár et al, 2017;Januschke et al, 2002;Zimyanin et al, 2008). As will be discussed in detail below, RNAs are also transported by molecular motors along microtubule arrays to the vegetal pole of the Xenopus oocyte (Gagnon et al, 2013;Messitt et al, 2008).…”
Section: Mechanisms Of Rna Localizationmentioning
confidence: 99%
“…RNA granules have long been observed to traffic within neuronal axons and dendrites (Knowles et al, 1996;Gopal et al, 2017). While their transport requires both microtubules and motor proteins, how membraneless RNA granules are tethered to transport machinery remains incompletely understood (Clark et al 2007;Davidovic et al 2007;Dictenberg et al 2008;Dienstbier et al 2009;Dix et al 2013;Gá spá r et al 2017;Gagnon et al 2013).…”
Section: Introductionmentioning
confidence: 99%